(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The rapid growth of Internet-based applications like social media platforms and blogs has resulted in comments and reviews regarding everyday routines. The process of collecting and analyzing people’s opinions, thoughts, and impressions concerning various topics, products, subjects, and services are known as sentiment analysis. People’s opinions can help corporations, governments, and individuals obtain information and make decisions based on those opinions. However, the sentiment analysis and evaluation procedure are full of challenges. These hardships make it challenging to accurately interpret sentiments and figure out the appropriate sentiment polarity. Sentiment analysis employs natural language processing and text mining to recognize and extract subjective information from text. This article offers a thorough explanation of the method for completing this task as well as sentiment analysis applications. Then, to fully comprehend the benefits and drawbacks of each method, it assesses, contrasts, and investigates them. To define future directions, the difficulties of sentiment analysis are finally examined.